(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Every successful piece of writing, from a novel to a technical report, relies on two fundamental principles to guide the reader from confusion to comprehension: cohesion and coherence. While often used interchangeably in casual discourse, these terms represent distinct layers of textual unity. Understanding their individual roles, and more importantly, their complex relationship, is crucial for any effective writer. Simply put, cohesion is the visible stitching that holds the sentences together, while coherence is the underlying design that makes the entire tapestry meaningful. The central challenge, or the "problem of correlation," lies in the fact that a text can be rich in one yet poor in the other, leading to a breakdown in communication.